The Bee Community of Cannabis sativa and Corresponding Effects of Landscape Composition. Issue 1 (2nd December 2019) - Flicker, Nathaniel Ryan; Poveda, Katja; Grab, Heather
Abstract: Industrial hemp, Cannabis sativa (Cannabaceae), is a newly introduced and rapidly expanding crop in the American agricultural landscape. As an exclusively wind-pollinated crop, hemp lacks nectar but produces an abundance of pollen during a period of floral dearth in agricultural landscapes. These pollen resources are attractive to a range of bee species but the diversity of floral visitors and their use of hemp across a range of agricultural contexts remains unclear. We made repeated sweep net collections of bees visiting hemp flowers on farms in New York, which varied in both landscape context and phenotypic traits of hemp varieties. We identified all bee visitors to the species level and found that hemp supported 16 different bee species. Landscape simplification negatively impacted the abundance of bees visiting hemp flowers but did not affect the species richness of the community. Plant height, on the other hand, was strongly correlated with bee species richness and abundance for hemp plots with taller varieties attracting a broader diversity of bee species. Because of its temporally unique flowering phenology, hemp has the potential to provide a critical nutritional resource to a diverse community of bees during a period of floral scarcity and thereby may help to sustain agroecosystem-wide pollination services for other crops in the landscape. As cultivation of hemp increases, growers, land managers, and policy makers should consider its value in supporting bee communities and take its attractiveness to bees into account when developing pest management strategies.